Olympos in Lycia: A Novel Assessment of its History and Localization in Light of Recent Archaeological and Epigraphical Research - (:unkn) unknown (KOC UNIV SUNA & INAN KIRAC RES CTR MEDITERRANEAN CIVILIZATIONS-AKMED, 2020)
Olympos is located on the eastern coast of Lycia, one of the ancient regions of Western Anatolia. It was one of the principal cities in the Lycian League, along with five others, and entitled to three votes. Archaeological excavations and surveys that started in 1998 and continued until today have unearthed much scientific data that illuminate the unknowns of the city and increase our knowledge of the Hellenistic, Roman and Byzantine periods of Olympos. Particular examples of archaeological and epigraphic data, which will most contribute to the debate regarding the localization of Olympos in Lycia, will be discussed in this article.
Keywords: Lycia; Olympos; Corycus; Mount Musa